The Comparison of Teaching Methodologies of Past and Present - qizi, Dushatova Shohsanam Baxtiyor; qizi, O’rmonjonova Ozoda Vohidjon (Research Parks Publishers, 2023)
I started learning English seven years ago and am now working as a teacher. In fact, teaching methodology has changed a lot from that period. At that time teachers were focused on practicing Cambridge books to prepare the student for the exams. They said that “the number of practice tests that you have done will show your result in the exam.” But now most teachers are focused on developing students’ general skills by doing passive things.